Media Pembelajaran Berbahan Loose Part Berbasis STEAM Dapat Membangun Merdeka Belajar Pada Anak Usia Dini - Purwanti Purwanti; Zulkarnaen Zulkarnaen (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
The purpose of this study is to analyze how learning media with media made from loose parts are an effort to build independent early childhood learning. This research method is a descriptive qualitative research. Research data collection techniques are by observation and interviews. The research was conducted at Aisyiyah Bustanul Athfal 1 Kindergarten Wonosegoro with a total of 16 research subjects consisting of 11 female students and 5 male students. The research steps started from lesson planning to learning evaluation and follow-up. The results showed that learning with loose part media can provide freedom to play and learn so that it can build independent early childhood learning. This can be seen from increasing children's creativity, encouraging children to be active in their learning, increasing children's independence, training children's ability to work together, and building self-confidence in children. The teacher's strategy is to use loose teachers to arrange a comfortable play environment for children. Part of learning is that children are free to determine the play activities and materials they want.